Prolactin concentrations during aripiprazole treatment in relation to sex, plasma drugs concentrations and genetic polymorphisms of dopamine D2 receptor and cytochrome P450 2D6 in Japanese patients with schizophrenia - Nagai, Goyo; Mihara, Kazuo; Nakamura, Akifumi; Suzuki, Takeshi; Nemoto, Kenji; Kagawa, Shoko; Ohta, Ikuya; Arakaki, Hajime; Kondo, Tsuyoshi (Psychiatry and clinical neurosciences, 2012)
Aims The authors investigated the correlation between prolactin concentrations during aripiprazole treatment and various factors, including age, sex, plasma concentrations of aripiprazole and its active metabolite, dehydroaripiprazole, and genetic polymorphisms of dopamine D2 receptor (DRD2) and cytochrome P450(CYP)2D6. Methods The subjects were 70 inpatients with schizophrenia (36 men and 34 women), receiving fixed doses of aripiprazole (24 mg in 45 cases and 12 mg in 25 cases) for periods of between 2 and 30 weeks. Prolactin concentrations were measured by chemiluminescence immunoassay. Plasma concentrations of aripiprazole and dehydroaripiprazole were measured using liquid chromatography with mass spectrometric detection. The genotypes of Taq1A, −141C Ins/Del DRD2 and CYP2D6 were detected by polymerase chain reaction methods. Results Prolactin concentrations were significantly higher in women than in men (8.9 ± 7.5 vs 3.4 ± 3.0 ng/mL, P < 0.001). No correlations were found between prolactin concentrations and plasma concentrations of aripiprazole, dehydroaripiprazole or the sum of the two compounds. Prolactin concentrations were not affected by any polymorphism. Conclusion The present study suggests that only sex plays a significant role in prolactin concentrations during aripiprazole treatment.